Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) khai triển được 2sin2+2cos2=2(sin2+cos2=2.1=2
b)cot2-cos2.cot2=cot2(1-cos2)=cot2.sin2=cos2/sin2.sin2=cos2
c)sin.cos(tan+cot)=sin.cos.tan+sin.cos.cot=sin.cos.sin/cos+sin.cos.cos/sin=sin2+cos2=1
d)tan2-tan2.sin2=tan2(1-sin2)=tan2.cos2=sin2/cos2.cos2=sin2
a) ta có : \(sin\alpha.cos\alpha\left(tan\alpha+cot\alpha\right)=sin\alpha.cos\alpha\left(\dfrac{sin\alpha}{cos\alpha}+\dfrac{cos\alpha}{sin\alpha}\right)\)
\(=sin^2\alpha+cos^2\alpha=1\)
b) ta có : \(\left(sin^2\alpha+cos^2\alpha\right)^2+\left(sin\alpha-cos\alpha\right)^2\)
\(=1^2+1-2sin\alpha.cos=2\left(1-2sin\alpha.cos\alpha\right)\)
c) ta có : \(tan^2\alpha-sin^2\alpha.tan^2\alpha=tan^2\alpha\left(1-sin^2\alpha\right)\)
\(=\dfrac{sin^2\alpha}{cos^2\alpha}.cos^2\alpha=sin^2\alpha\)
\(A=sin^210+sin^220+sin^230+sin^280+sin^270+sin^260=sin^210+sin^220+sin^230+cos^210+cos^220+cos^230=1+1+1=3\)\(B=\left(1+tan^2\alpha\right)\left(1-sin^2\alpha\right)+\left(1+cot^2\alpha\right)\left(1-cos^2\alpha\right)=\dfrac{1}{cos^2\alpha}.cos^2\alpha+\dfrac{1}{sin^2\alpha}.sin^2\alpha=1+1=2\)
\(a,1-sin^2\alpha=cos^2\alpha\)
\(b,\left(1-cos\alpha\right)\left(1+cos\alpha\right)=1-cos^2\alpha=sin^2\alpha\)
\(c,1+sin^2\alpha+cos^2\alpha=1+1=2\)
\(d,sin\alpha-sin\alpha.cos^2\alpha=sin\alpha.\left(1-cos^2\alpha\right)=sin\alpha.sin^2\alpha=sin^3\alpha\)
\(e,sin^2\alpha+cos^2\alpha+2sin^2\alpha.cos^2\alpha\)
\(=1+2sin^2\alpha.cos^2\alpha\)
\(\frac{sin^2\alpha}{cos\alpha.\left(1+\frac{sin\alpha}{cos\alpha}\right)}-\frac{cos^2\alpha}{sin\alpha.\left(1+\frac{cos\alpha}{sin\alpha}\right)}=\frac{sin^2\alpha}{cos\alpha+sin\alpha}-\frac{cos^2\alpha}{sin\alpha+cos\alpha}=\frac{\left(sin\alpha+cos\alpha\right).\left(sin\alpha-cos\alpha\right)}{sin\alpha+cos\alpha}=sin\alpha-cos\alpha\)
Lời giải:
Gọi biểu thức trên là $P$. Ta có:
$P=(1+\frac{\sin ^2a}{\cos ^2a})(1-\sin ^2a)-(1+\frac{\cos ^2a}{\sin ^2a})(1-\cos ^2a)$
$=\frac{\sin ^2a+\cos ^2a}{\cos ^2a}.\cos ^2a-\frac{\sin ^2a+\cos ^2a}{\sin ^2a}.\sin ^2a$
$=(\sin ^2a+\cos ^2a)-(\sin ^2a+\cos ^2a)$
$=0$